INFLUENCE OF ANTIBIOTICS ON IN VITRO MORPHOLOGICAL CHARACTERS OF RECALCITRANT POTATO CULTIVAR KUFRI JYOTI - Venkatasalam, E P; Latawa, Jyoti; Chakrabarti, S K; Singh, B P (Potato Journal, 2016)
The effect of three different antibiotics viz., carbenicillin (50, 75, 100 and 125 mg/l), cephotaxime (100, 150, 200 and 250 mg/l) and kanamycin (30, 40, 50 and 60 mg/l) against bacterial contaminants (Bacillus pumilus) and in vitro shoot growth of potato (Solanum tuberosum L.) recalcitrant cultivar Kufri Jyoti was evaluated. Efficacy of antibiotics to control bacterial contaminant differed greatly; cephotaxime and carbenicillin were found to be more effective as compared to kanamycin. The type of antibiotics and their concentrations affected the growth, morphological characters of the microplant and the bacterial contaminations. The medium containing carbenicillin @ 75 mg/l and cephotaxime @ 150 mg/l significantly accelerated the microplant height, number of leaves, nodes and roots; root length and fresh as well as dry mass. For most of the microplant growth parameters there was no significant difference between carbenicillin @ 50 mg/l and cephotaxime @ 100 mg/l and negligible bacterial contamination was observed at these concentrations. Higher concentration beyond this level however, had detrimental effect on the growth and morphology of microplants. The cost of incorporating carbenicillin was double as compared to cephotaxime per liter of culture medium.